Thickness of the Stifle Joint Articular Cartilage in Different Large Animal Models of Cartilage Repair and Regeneration. (December 2021) - Ruediger, Tina; Horbert, Victoria; Reuther, Anne; Kumar Kalla, Pavan; Burgkart, Rainer H.; Walther, Mario; Kinne, Raimund W.; Mika, Joerg
Objective: Regulatory guidelines for preclinical cartilage repair studies suggest large animal models (e.g., sheep, goat, [mini]-pig, or horse) to obtain results representative for humans. However, information about the 3-dimensional thickness of articular cartilage at different implantation sites in these models is limited. Design: To identify the most suitable site for experimental surgery, cartilage thickness at the medial femoral condyle (MFC), lateral femoral condyle (LFC), and trochlea in ovine, caprine, and porcine cadaver stifle joints was systematically measured using hematoxylin-eosin staining of 6 µm paraffin sections and software-based image analysis. Results: Regarding all ventral-dorsal regions of the MFC, goat showed the thickest articular cartilage (maximal mean thickness: 1299 µm), followed by sheep (1096 µm) and mini-pig (604 µm), with the highest values in the most ventral and dorsal regions. Also for the LFC, the most ventral regions showed the thickest cartilage in goat (maximal mean thickness: 1118 µm), followed by sheep (678 µm) and mini-pig (607 µm). Except for the mini-pig, however, the cartilage thickness on the LFC was consistently lower than that on the MFC. The 3 species also differed along the transversal measuring points on the MFC and LFC. In contrast, there were no consistent differences for the regional cartilage thickness of the trochlea among goat and sheep (≥780 µm) and mini-pig (≤500 µm). Conclusions: Based on their cartilage thickness, experimental defects on goat and sheep MFC may be viable options for preclinical cartilage repair studies, in addition to well-established horse models.